2019
DOI: 10.24018/ejbmr.2019.4.3.38
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Online Banking Adoption on Bank’s Profitability: Evidence from Bangladesh

Abstract: The rise in information technologies has transformed banking industry worldwide. To stay competitive, banks are introducing internet banking with the motive to achieve higher productivity and efficiency, reduce cost and increase profit. In Bangladesh, the impact of this new distribution channel in improving bank’s performance is yet to be measured. It is against this backdrop this research is conducted to identify whether performance of banks that has adopted internet banking is different from banks yet to ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Such risks must be addressed tactfully to minimize SSC failure. Server failure holds the third position with a closeness coefficient value near to the value of database hack.A recent study shows an upward trend in online banking in Bangladesh, including transactions through the internet, mobile phones, ATMs, and nominated agents [ 61 ]. All these services can be severely affected if any server failure occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Such risks must be addressed tactfully to minimize SSC failure. Server failure holds the third position with a closeness coefficient value near to the value of database hack.A recent study shows an upward trend in online banking in Bangladesh, including transactions through the internet, mobile phones, ATMs, and nominated agents [ 61 ]. All these services can be severely affected if any server failure occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the banks as companies that operate for profit, the research did not show the impact of social media activity on bank performance. Such analysis has been conducted by other researchers but concerning Internet adoption (Hernando and Nieto 2007;De Young et al 2007;Yang et al 2018;Islam et al 2019). The results were mostly inconclusive, as bank performance is affected by a very broad spectrum of factors, and emphasizing only one of them seemed too selective.…”
Section: Discussionmentioning
confidence: 99%
“…Online banking services such as balance enquiry, printing statements, fund transfers to other accounts and bill payments are becoming famous nowadays (Fo & Ak, 2015). The study conducted by Islam et al (2019b) in Bangladesh on electronic banking found that banking, like other sectors, has passed through many transformations from traditional banking to online banking. The main reason is the competitive business environment, which requires a business to be innovative to serve customers.…”
Section: Literature Reviewmentioning
confidence: 99%